RESULTS OF THE STUDY OF THE ACID-PRODUCING FUNCTION OF H. PYLORI-ASSOCIATED DISEASES OF THE STOMACH - J.A. Ismailova; A.A. Yusupbekov (Scholar Express Journals, 2023)
The authors studied the acid-producing function of the stomach in H. pyloriassociated pathologies. According to the study, the studied pathology was characterized by the presence of a hyperacid state of gastric juice in chronic non-atrophic gastritis according to the pH values. Also, in patients with atrophic gastritis in gastric juice, sub- and decompensated violations of the acid neutralizing function of the stomach are noted. At the same time, the arch and antrum of the stomach are the most informative parameters for measuring pH in the stomach.
Keywords: H. pylori-associated diseases of the stomach; pH in the stomach; acid neutralizing function; antrum